2017
DOI: 10.1016/j.bjm.2017.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial efficacy of nisin, bacteriophage P100 and sodium lactate against Listeria monocytogenes in ready-to-eat sliced pork ham

Abstract: The effectiveness of bacteriophage P100, nisin and sodium lactate, individually and in combination, in inhibiting Listeria monocytogenes in ready-to-eat pork ham slices was assessed. The antimicrobials were applied to the surfaces of ready-to-eat pork ham slices, which were inoculated with a mixture of L. monocytogenes. Among the individual antimicrobial treatments, bacteriophage P100 was the most effective, decreasing L. monocytogenes to undetectable levels at zero and 72 h post-infection. Sodium lactate was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 38 publications
0
20
0
1
Order By: Relevance
“…In this context, the application of bacteriophages to assorted foods (including RTE foods) has been shown, by several investigators, to be effective at reducing contamination with L. monocytogenes ( Table 1 ). For example, a commercial monophage preparation (i.e., phage preparation consisting of one single phage) targeting Listeria was reported to be effective in reducing the levels of L. monocytogenes in sliced ham, and to be superior to nisin and sodium lactate, when compared at the storage abuse temperature of 6–8 °C [ 47 ]. A similar study by Chibeu and colleagues (2013) demonstrated that the same monophage preparation was also able to reduce L. monocytogenes on the surface of other deli meats [ 44 ].…”
Section: Phage Biocontrol For Targeting Common Foodborne Bacterialmentioning
confidence: 99%
“…In this context, the application of bacteriophages to assorted foods (including RTE foods) has been shown, by several investigators, to be effective at reducing contamination with L. monocytogenes ( Table 1 ). For example, a commercial monophage preparation (i.e., phage preparation consisting of one single phage) targeting Listeria was reported to be effective in reducing the levels of L. monocytogenes in sliced ham, and to be superior to nisin and sodium lactate, when compared at the storage abuse temperature of 6–8 °C [ 47 ]. A similar study by Chibeu and colleagues (2013) demonstrated that the same monophage preparation was also able to reduce L. monocytogenes on the surface of other deli meats [ 44 ].…”
Section: Phage Biocontrol For Targeting Common Foodborne Bacterialmentioning
confidence: 99%
“…Phage P100, when used as an antimicrobial treatment, proved to be very effective in inactivating and inhibiting the growth of L. monocytogenes in sliced pork ham. Under refrigerated conditions, the combination of P100 bacteriophage and nisin bacteriocin was more effective as a bioconserver against L. monocytogenes than nisin alone (Figueiredo & Almeida, 2017). More recently, the synergistic potential between endolysin, PlyP100, and nisin has also been assessed for anti-Listeria activity.…”
Section: Bacteriophages Associated With Natural Antibacterial Substancesmentioning
confidence: 99%
“…While the application of phages for medical purposes has a long tradition in different parts of the world [68,69,70], in the food sector phages have been commercially available as biological disinfectants against various foodborne pathogens as well as food spoilage bacteria, for about two decades [9,24,71,72,73,74,75,76,77,78,79]. Among their many advantages, the use of phages as biological disinfectants is highly advantageous compared to physical or chemical disinfectant measures due to their limited to none impact on sensory or quality parameters of the processed food [77,80,81].…”
Section: Commercial Phage Products Their Application Field and Lementioning
confidence: 99%